Access to healthcare insurance and healthcare services among syringe exchange program clients in Massachusetts: qualitative findings from health navigators with the iDU ("I do") Care Collaborative. - Stopka, Thomas J.; Hutcheson, Marguerite.; Donahue, Ashley. (2017)
Background: Little is known about access to health insurance among people who inject drugs (PWID) who attend syringe exchange programs (SEPs). The goal of the current study was to assess perceptions of SEP staff, including health navigators and program managers, on access to health insurance and healthcare access among SEP clients following implementation of state and federal policies to enhance universal healthcare access in Massachusetts.; Keywords: Syringe exchange programs, Health insurance, People who inject drugs, Massachusetts, Substance use, Hepatitis C virus.; Springer Open.